Liberalized Markets Have More Stable Exchange Rates : Short-Run Evidence From Four Transition Countries - Bulir, Ales (IMF Working Papers; Working Paper ;, 2004)
The paper looks at the hypothesis that financial market liberalization can create a basis for more stable exchange rates, as deviations of exchange rates from equilibrium levels bring forth stabilizing flows of liquidity. This "endogenous liquidity" hypothesis suggests that opening financial markets militates in favor of exchange rate flexibility by increasing the viability of a floating regime, as well as making it more difficult to maintain a peg. The paper examines this hypothesis in a sample of four transition economies and finds that exchange rates tend to return faster to their Hodrick-Prescott-based values where markets are liberalized. The results suggest that early and successful foreign exchange liberalization pays off in terms of depth of the market and, hence, faster adjustment of exchange rate to shocks. Moreover, it implies that central banks should not be overly concerned with short-run volatility of their national exchange rates, given the self-correcting tendencies.